Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
In his book entitled „Man’s Problem”, Martin Buber discussesthe anthropological status of our times mentioning two factors,which have considerably influenced the comprehension, existence,identity and man’s future; both of them exhibit traits of crisis.The first one can be identified in terms of sociology. Previousorganic forms of direct contact between humans are collapsingrapidly. Man, through the continuously appearing variety of institutions,associations, parties, through globalisation, enters theworld of anonymity, which excludes the possibility of direct relationsin small groups, in communities that gave him the senseof safety, peace at heart. These communities, first of all, refer tothe family, but also to the craft guild, the village and town commune,as well as other associations. In these, living tradition wascultivated and the history was recollected; therefore, they becamethe place where the sense of one’s own identity could befelt.